Ethnographic study of ICT-supported collaborative work routines in general practice - Myall Michelle; Greenhalgh Trisha; Swinglehurst Deborah; Russell Jill (BMC, 2010)
Abstract Background Health informatics research has traditionally been dominated by experimental and quasi-experimental designs. An emerging area of study in organisational sociology is routinisation (how collaborative work practices become business-as-usual). There is growing interest in the use of ethnography and other in-depth qualitative approaches to explore how collaborative work routines are enacted and develop over time, and how electronic patient records (EPRs) are used to support collaborative work practices within organisations. Methods/design Following Feldman and Pentland, we will use 'the organisational routine' as our unit of analysis. In a sample of four UK general practices, we will collect narratives, ethnographic observations, multi-modal (video and screen capture) data, documents and other artefacts, and analyse these to map and compare the different understandings and enactments of three common routines (repeat prescribing, coding and summarising, and chronic disease surveillance) which span clinical and administrative spaces and which, though 'mundane', have an important bearing on quality and safety of care. In a detailed qualitative analysis informed by sociological theory, we aim to generate insights about how complex collaborative work is achieved through the process of routinisation in healthcare organisations. Discussion Our study offers the potential not only to identify potential quality failures (poor performance, errors, failures of coordination) in collaborative work routines but also to reveal the hidden work and workarounds by front-line staff which bridge the model-reality gap in EPR technologies and via which "automated" safety features have an impact in practice.